The biological sciences section program at the 60th Annual Meeting of the Gerontological Society of America. - Effros RB; Austad S; Blau H; Chesselet M; Ingram D; Johnson TE; Kaeberlein M; Lundblad V; McCarter R; McElhaney J; Saag M; Effros, Rita B; et al. (Journals of Gerontology Series A: Biological Sciences & Medical Sciences, 2008)
In this era of genomics and other exciting technical advances, research on the biology of aging is undergoing a renaissance. This report summarizes 10 cutting-edge areas of research covered in symposia that spanned such topics as stem cells, novel vaccine strategies, nutritional sensing, new concepts of Parkinson's disease, high throughput screening for aging interventions, manipulating telomerase in cancer and immunodeficiency, synergy between aging and HIV disease, and epigenetic influences on aging. Novel animal models, including those showing no evidence of aging, as well as ethical and political implications of embryonic stem cells and alternative medicine are also discussed.